2017
DOI: 10.3390/ijms18040771
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress and Oxidative Stress: A Vicious Nexus Implicated in Bowel Disease Pathophysiology

Abstract: The endoplasmic reticulum (ER) is a complex protein folding and trafficking organelle. Alteration and discrepancy in the endoplasmic reticulum environment can affect the protein folding process and hence, can result in the production of misfolded proteins. The accumulation of misfolded proteins causes cellular damage and elicits endoplasmic reticulum stress. Under such stress conditions, cells exhibit reduced functional synthesis, and will undergo apoptosis if the stress is prolonged. To resolve the ER stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
154
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(158 citation statements)
references
References 132 publications
(273 reference statements)
3
154
0
1
Order By: Relevance
“…Meanwhile, changes in protein folding pathways produces an ROS imbalance, indirectly disturbing both ER and redox homeostasis and this response can be reversed by antioxidants like thyme vulgaris. 13,14 Thyme is a natural herb belongs to lamiacea family. It has antioxidant properties and free radical scavenger activity.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, changes in protein folding pathways produces an ROS imbalance, indirectly disturbing both ER and redox homeostasis and this response can be reversed by antioxidants like thyme vulgaris. 13,14 Thyme is a natural herb belongs to lamiacea family. It has antioxidant properties and free radical scavenger activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, chronic and excessive ROS production activates host inflammatory pathways and results in oxidative stress [133]. During IBD development, oxidative stress contributes to chronic inflammation and dysbiosis, control of oxidative stress may help to maintain the intestinal homeostasis [134, 135]. ROS can induce inflammation by triggering JNK, protein kinase C, growth factor tyrosine kinase receptor, and extracellular signal-regulated kinase signaling pathways.…”
Section: Ros and Diseasesmentioning
confidence: 99%
“…ER stress is a condition that disrupts normal protein folding via some pathologic and physiologic processes, such as I/R, calcium dyshomeostasis, inflammation, and reactive oxygen species accumulation; this disruption results in misfolded and unfolded protein accumulation in the ER lumen (22). With stimulation by ER stress, the unfolded protein response is sequentially activated through 3 signaling pathways, the PRKR-like ER kinase (PERK), inositol-requiring enzyme 1a (IRE1a), and activating transcription factor 6 (ATF6) pathways (23). Many studies have suggested that ER stress is involved in various renal diseases, including acute kidney injury, glomerulonephritis, renal I/R, and chronic kidney disease.…”
mentioning
confidence: 99%